Conductive polymer composites from polylactic acid/thermoplastic polyurethane filled with carbon black - Buys, Yose Fachmi; Udin, Nur Suhaida (2015)
In order to develop environmentally friendlier conductive polymer composites, polylactic acid (PLA), toughened with thermoplastics polyurethane (TPU), were filled with conductive carbon black (CB). Electrical and mechanical properties, as well as morphology of the composites were examined. Dynamic mechanical analysis measurement of PLA/TPU blends showed two glass transition temperatures appeared, indicating immiscibility of the blends. Scanning electron microscopy observation revealed the morphology of spherical TPU droplets dispersed in PLA for PLA90/TPU10 blend, and co-continuous structure for PLA70/TPU30 blend matrices. Electrical resistance measurement showed that the composites with PLA70/TPU30 matrices had lower percolation threshold, compared to PLA/CB, TPU/CB, and PLA90/TPU10/CB systems, indicating that double percolation effect occurred in PLA70/TPU30/CB systems. In addition, improvement of impact strength of PLA by addition of TPU was also confirmed.